Highly dynamic rotational molding of thin-walled larynx models for fluid dynamic modelling - Schlicht, Samuel; Kaufmann, Anke; Tur, Bogac; Kniesburges, Stefan; Drummer, Dietmar (Proceedings of the 13th International Conference on Voice Physiology and Biomechanics, 2024)
Objectives / Introduction: The experimental investigation of the flow-structure coupling represents a significant challenge in otolaryngology/phoniatrics, which is often performed with human and animal-derived specimens showing a rapid degradation of relevant mechanical and dynamic properties. The synthetic, elastomer-based replication of laryngeal mechanics remains challenging due to the complex, non-linear mechanical properties of the larynx. Complementing previously described approaches relying on the multi-layered molding of laryngeal structures, the presented approach is based on the adhesion-controlled highly dynamic rotational molding of ultra-soft silicones, yielding film thicknesses as low as 10 micrometers with ultra-soft properties and high geometric precision. Methods: Relying on rotational frequencies exceeding 30 Hz, the manufacturing of thin-walled laryngeal models becomes feasible. Based on the multi-layered manufacturing, the targeted modification of superficial mechanics with ultra-soft properties is obtained while enabling the replication of complex geometries and undercuts. The subsequent elastomer- and hydrogel-based modification of molded silicone structures allows for adapting the mechanical and dynamic properties of the vocal folds, representing a promising approach for the facilitated modeling of laryngeal dynamics. Results: Based on the described method, first prototypes of vocal fold models were manufactured. These prototypes were evaluated in a customized experimental setup by measuring the vocal folds’ dynamics, the subglottal pressure and the generated sound signal. Conclusions: While the manufacturing of ultra-soft laryngeal models with a high geometric precision is usually impaired due to material-specific limitations of ultra-soft polymers, employing the multi-layered manufacturing of elastomers of varying mechanical properties allows to mimic the biomechanical properties of the vocal folds while minimizing adverse adhesive effects and the aging of models<br